Genetic Analyses, BSA-Seq, and Transcriptome Analyses Reveal Candidate Genes Controlling Leaf Plastochron in Rapeseed (Brassica napus L.) - Mengfan Qin; Xiang Liu; Jia Song; Feixue Zhao; Yiji Shi; Yu Xu; Zhiting Guo; Tianye Zhang; Jiapeng Wu; Jinxiong Wang; Wu Li; Keqi Li; et al. (Plants)
The leaf plastochron serves as an indicator of the rate of leaf appearance, biomass accumulation, and branch number, while also impacting plant architecture and seed yield. However, research on the leaf plastochron of crops remains limited. In this study, 2116C exhibited a rapid leaf plastochron compared to ZH18 during both rosette and bud periods. There were significant positive correlations among the leaf plastochron and primary branch number of the F2 populations (r ranging from 0.395 to 0.635, p < 0.01). Genetic analyses over two years demonstrated that two equally dominant genes might govern the leaf plastochron. Through bulk segregant analysis sequencing (BSA-seq), three novel genomic intervals were identified on chromosomes A02 (9.04–9.48 Mb and 13.52–13.66 Mb) and A04 (19.84–20.14 Mb) of ZS11 and Darmor-bzh reference genomes. By gene functional annotations, single-nucleotide variation (SNV) analyses, transcriptome data from parents, genetic progeny, and natural accessions, we identified ten candidate genes within the intervals, including FLOWERING LOCUS T, RGL1, MYB-like, CYP96A8, BLH3, NIT2, ASK6, and three CLAVATA3/ESR (CLE)-related genes. These findings lay the molecular foundation for further exploration into the leaf plastochron and the implications in plastochron-related breeding in rapeseed.